Beta-sitosterol and its derivatives repress lipopolysaccharide/d-galactosamine-induced acute hepatic injury by inhibiting the oxidation and inflammation in mice. Issue 9 (15th May 2018) - Yin, Yongxia; Liu, Xiaofeng; Liu, Jinping; Cai, Enbo; Zhu, Hongyan; Li, Haijun; Zhang, Lianxue; Li, Pingya; Zhao, Yan
Graphical abstract: Highlights: Four kinds of new beta-sitosterol derivatives were synthesized. New compounds exhibit safe and non-toxic properties. Effect of Sit-N on anti-acute liver injury in mice was confirmed. Effect of Sit-N against acute liver injury mediated by TLR4 and Nrf2 pathways. Abstract: Beta-sitosterol (Sit) widely exists in natural plants, is classed as phytosterol and known as the "key of life". Most pharmacological studies and clinical applications are limited because of the fact that Sit is difficult to be solved. Therefore, it is viable to enhance pharmacologic activities of Sit by using its derivatives which can be obtained through the modification of Sit. In this study, 4 kinds of new Sit derivatives were obtained by the esterification reaction. Further, the hepatoprotective effects of Sit and its derivatives were investigated against acute liver injury induced by lipopolysaccharide/d -galactosamine (LPS/GalN) in mice and its mechanism was illustrated by western blot analysis and real-time PCR. The results demonstrated that among its derivatives, 2-naphthoyl Sit ester (Sit-N) (50 mg/kg) showed the strongest activities against acute liver injury. Final experimental results showed that Sit-N significantly decreased the serum activity of aspartate transaminase (AST) and alanine aminotransferase (ALT); Sit-N also markedly reduced tumor necrosis factor (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) levels. Meanwhile, Sit-N drastically improved the activities of antioxidant enzymes such as superoxide dismutase (SOD), glutathione (GSH) and catalase (CAT), and suppressed the expression of malondialdehyde (MDA). Results also displayed that over-expression of Toll like receptor 4 (TLR4) and nuclear factor-kappa B (NF-κB) induced by LPS/Gal N were inhibited by Sit-N. Meanwhile, the expression of nuclear respiratory factor2 (Nrf2) and heme oxygenase-1 (HO-1) were enhanced. The results all above verified the effectiveness of Sit-N against acute liver injury induced by LPS/GalN mediated by TLR4 and Nrf2 pathways.